Missing Link : The image of man in contemporary photography - Doswald, Christoph; Aigner, Carl; Banz, Stefan; Koerfer, Thomas; Kozloff, Max; Peters, Kathrin; Pfister, Thomas; Wulffen, Thomas; Kunstmuseum Bern, Bern (Zürich : Edition Stemmle, 2000)
Abdu'Allah, Faisal ; Abramovic, Marina ; Araki, Nobuyoshi ; Banz, Stefan ; Bara, Tina ; Barbier, Gilles ; Barney, Matthew ; Beecroft, Vanessa ; Billingham, Richard ; Breuning, Olaf ; Brus, Günther ; Buetti, Daniel ; Burkhard, Balthasar ; Byars, James Lee ; et al.
Missing Link - Bilder in der Fotografie at Kunstmuseum Bern, 1999
kunstcatalogus